The development of the shadow economy under changing tax systems and structures: Some theoretical and empirical results for Austria - Friedrich Schneider; Reinhard Neck (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
In this paper we investigate how different tax systems and structures affect the extent of the shadow economy. First, we formulate a simple theoretical microeconomic raodel of household behavior, where the household can participate in the official and in the shadow economy. Using comparative statics, we show that a measure of "coraplexity" of the tax system affects participation in the shadow economy negatively, i.e., a more "complex" tax system implies, ceteris paribus, a smaller labor supply in the shadow economy. Next, we analyze the determinants of the shadow economy empirically for Austria. Various methods to estimate the size of the shadow economy are discussed. Empirical results for Austria obtained by using the currency demand approach are presented. Finally, we examine three case studies to show quantitatively how the size of the shadow economy can be influenced by changes in the tax structures.
Keywords: H26; 330